Social Sphere of Kiselevo on Eve of Gaining City Status (Local Periodicals) - A. Yu. Karpinets (Научный диалог, 2023)
The article is devoted to the development of the Kiselevsk village in 1935, the last year when Kiselevsk existed in the status of a workers’ settlement. The issue of improving the living and communal conditions of the miners of the Kiselevsky mine and their families is being considered. Attention is paid to the problems of the relationship between the material well-being of workers and the increase in labor productivity. The problems of housing and communal services, the development of the branches of upbringing, education and health care are characterized. The methods of ensuring the food security of miners are determined. Specific measures to improve the quality of life of workers in the context of the transformation of the settlement from a working settlement into a city are demonstrated. The novelty of the study is seen in the fact that for the first time, based on the processing of materials from the periodical press, the social sphere of the Kiselyovsky mine was characterized in detail in the mid-1930s. The relevance of the study is due to its scientific and social significance. The first is determined by the fact that this kind of research is undertaken for the first time. The second is connected with the need to draw attention to the problems of sustainable socio-economic development of the city of Kiselevsk at the present time.